KAJIAN STURUTUR CERITA RAKYAT BONE MALEI PADA MASYARAKAT BUTON - Yeyen Cinta Lestari; Irianto Ibrahim; Sulfiah (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2024)
The purpose of this research is to describe and analyze the structure contained in the folklore of Bone Malei in the Butonese people. This research is a field research, using a qualitative descriptive method. The data used in this study are in the form of information and recordings obtained about the folklore of Bone Malei. The source of data in this research is the community or informants who know about the folklore of Bone Malei. Data collection techniques interview techniques. The data analysis technique uses the Folklore approach. The results showed that the study of the structure of Buton Bone Malei Folklore consisted of characters, main characters and additional characters. The main character is played by La Kilaponto and the additional characters are played by La Bolontio, Raja La Mulae and Wa Tampoidongi. In the following data, it is found that there is a plot underlying the formation of the study of the structure of the folklore of Buton Bone Malei, which is an advanced plot. As for the elements of the background, namely the setting of the place, namely, Buton, the Kingdom of Buton, Bone Tobungku, the beach and Labuan Tobelo. The time setting found is one day, the next day, a few moments later, a week later, and day after day, while the social setting is the heroism of the main character to quell crime.